PEMANFAATAN KOMPOS SOLID DAN MIKROORGANISME SELULOLITIK DALAM MEDIA TANAM PMK PADA BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN UTAMA - Swatop Pakpahan; Sampoerno '; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this study was to know the effect of the interaction of a solid compost utilization and cellulolytic microorganisms and to get the best effect on seedling growth of oil palm (Elaeis guineensis Jacq.) In the planting medium PMK in the main nursery.The experiment was conducted at the experimental farm of the Faculty of Agriculture, University of Riau from January 2015 to April 2015.The study arranged experimentally using Completely Randomized Design (CRD) factorial. The treatments consisting of two factors: the first factor utilization of solid compost consists of 4 levels as follows giving of solid compost (0, 25, 50 and 75) g/polybag plants and the second factor giving cellulolytic microorganisms consists of 3 levels as follows giving of MOS (0, 10 and 20) ml/polybag plants. Thus there are 12 combinations of treatment with repeated3timesthen obtained 36 experimental units.Parameters observed were the increase of seeds height, increase of humpconvolution, increaseofleaves, volume of root, rootshootratioanddry weightof oil palm seedlings.Data were analyzed statistically using ANOVA and followed by HSD at level of 5%.The results showed that the interaction of a solid compost utilization and giving of MOS significant effect on the overall observed parameters. Utilization of solid compost 75 g/polybag and giving MOS 20 ml/polybag showed the best result for the overall observed parameters. Keywords : Elaeis guineensis Jacq.,solid compost, cellulolytic microorganisms